Early Adverse Caregiving Experiences and Preschoolers' Current Attachment Affect Brain Responses during Facial Familiarity Processing: An ERP Study - Kungl, Melanie T.; Bovenschen, Ina; Spangler, Gottfried (Frontiers in Psychology, 2017)
When being placed into more benign environments like foster care, children from adverse rearing backgrounds are capable of forming attachment relationships to new caregivers within the first year of placement, while certain problematic social behaviors appear to be more persistent. Assuming that early averse experiences shape neural circuits underlying social behavior, neurophysiological studies on individual differences in early social-information processing have great informative value. More precisely, ERP studies have repeatedly shown face processing to be sensitive to experience especially regarding the caregiving background. However, studies on effects of early adverse caregiving experiences are restricted to children with a history of institutionalization. Also, no study has investigated effects of attachment security as a marker of the quality of the caregiver-child relationship. Thus, the current study asks how adverse caregiving experiences and attachment security to (new) caregivers affect early- and mid-latency ERPs sensitive to facial familiarity processing. Therefore, pre-school aged foster children during their second year within the foster home were compared to an age matched control group. Attachment was assessed using the AQS and neurophysiological data was collected during a passive viewing task presenting (foster) mother and stranger faces. Foster children were comparable to the control group with regard to attachment security. On a neurophysiological level, however, the foster group showed dampened N170 amplitudes for both face types. In both foster and control children, dampened N170 amplitudes were also found for stranger as compared to (foster) mother faces, and, for insecurely attached children as compared to securely attached children. This neural pattern may be viewed as a result of poorer social interactions earlier in life. Still, there was no effect on P1 amplitudes. Indicating heightened attentional processing, Nc amplitude responses to stranger faces were found to be enhanced in foster as compared to control children. Also, insecurely attached children allocated more attentional resources for the neural processing of mother faces. The study further confirms that early brain development is highly sensitive to the quality of caregiving. The findings are also relevant from a developmental perspective as miswiring of neural circuits may possibly play a critical role in children's psycho-social adjustment.